2001
DOI: 10.1086/322733
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Complications among 620 Consecutive Heart Transplant Patients at Stanford University Medical Center

Abstract: A total of 1073 infectious episodes (IEs) that occurred in 620 consecutive heart transplantation patients at Stanford Medical Center between 16 December 1980 and 30 June 1996 were reviewed. Infectious complications were a major cause of morbidity and mortality, second only to rejection as the cause of early deaths and the most common cause of late deaths. Of the IEs, 468 (43.6%) were caused by bacteria, 447 (41.7%) by viruses, 109 (10.2%) by fungi, 43 (4.0%) by Pneumocystis carinii, and 6 (0.6%) by protozoa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
202
5
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(233 citation statements)
references
References 31 publications
15
202
5
11
Order By: Relevance
“…Montoya et al reported, in heart transplant, that main bacterial infection sites were the lungs and urinary tract [10]. In our study, however, the most observed episode of Table 4.…”
Section: Discussioncontrasting
confidence: 46%
“…Montoya et al reported, in heart transplant, that main bacterial infection sites were the lungs and urinary tract [10]. In our study, however, the most observed episode of Table 4.…”
Section: Discussioncontrasting
confidence: 46%
“…The high-risk individuals of GNB infection are those with poor immunity resulted from chemotherapy, autoimmune disease, or immunosuppression treatment after transplantation (17,18). However, no prophylactic method for bacterial infection occurred is available.…”
Section: Discussionmentioning
confidence: 99%
“…The MMF dose was modified or treatment was terminated depending on all available information such as leukopenia <4000 leukocytes/mm 3 and/or severe lymphopenia and in certain cases, of severe infection. In case of blood count normalization, the dose of MMF was either individually enhanced or MMF was reinitiated in lower doses under careful monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…In the early period after orthotopic heart transplantation (HTx), patients are particularly vulnerable to rejection 1 and infectious complications 2,3 . Immunosuppressive and anti-infective drug prophylaxis consists of drugs with potentially myelotoxic effects.…”
Section: Introductionmentioning
confidence: 99%